Exploring the language of traffic signs in the Malaysian linguistic landscape: Its meaning / Lim Chia Wei … [et al.] - Lim, Chia Wei; Chan, Swee Heng; Abdullah, Ain Nadzimah; Rafik-Galea, Shameen (Universiti Teknologi MARA Cawangan Pahang, 2009)
A relatively new area of sociolinguistic research today focuses on linguistic landscape, in which linguistic elements that are emblematic of a society s identity are found and managed. The notion of linguistic land5cape has been given varied interpretations, in the sense of what constitutes a linguistic landscape and its presence in a local, global or multicultural selling. This systematic study has chosen to focus on just one dimension of social reality that is brought to life through a semiotic system found in the Malaysian public domain. A study of this nature helps to uncover an aspect of visual language use that contours a relationship between the goals of public authority and the end users in a civil society. Specifically, the study attempts to give expression and meaning to the use of traffic road signs, as visual language, from the point of view of school children who are nurtured by society in a number of ways to participate responsibly in the power dynamics of a vibrant social structure.